Length of stay of elderly in a Community Physical Activity Program and Associated Factors - Cristiane Kelly Aquino dos Santos; Glauber Rocha Monteiro; Josiene de Oliveira Couto; Roberto Jeronimo dos Santos Silva (Universidade Federal de Santa Catarina, 2017)
The registration or insertion of older adults in Community Physical Activity Programs does not guarantee their stay over time. The purpose of this study was to analyze the length of stay of elderly in a Community Physical Activity Program and associated factors. This epidemiologic observational study of retrospective cohort performed in Aracaju City, Brazil, included a sample of 526 older adults (477 females) aged 66.4 ± 5.4 years. To characterize the profile and length of stay of individuals, descriptive statistics was used. To analyze the length of stay, the Kaplan-Meier non-parametric survival, estimator was used. To verify the association between variables in the observed time, the Cox regression model was applied. Inverse ratio equation (1/OR) was used to facilitate the understanding of significant values when necessary. In all analyses, 95% confidence interval and p≤0.05 were used. In the first three months, stay rate of 58.1% (95% CI = 54.6 - 61.3) was observed, with a risk estimative = 41.82%. Females presented a 45% chance of stay (OR = 0.69; 95% CI = 0.51 - 0.93) and individuals identified with osteoporosis had 32% more chances of stay (OR = 0.74, 95% CI, = 0.60-0.91). Only 1% of subjects remained until the end of the cohort. The stay rate was low throughout all series; the period with higher quitting rates was the 3rd and the 12th months, being associated with the female stay sex and undiagnosed osteoporosis.